(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
Analysis of children’s speech is considered one of the most complex tasks in linguistics, and experiences related to this issue in world corpus studies are gathered in the CHILDES system. This article describes the issue of creating a database for the CHILDES system based on research aimed at studying children’s speech in the Uzbek language.